341 Alder Hey Experience of Paediatric Virtual Fracture Clinic During The COVID-19 Pandemic. (12th October 2021) - Stead, L; Ashraf, M; Gandham, S; Khattak, M; Talbot, C
Abstract: Introduction: The SARS-CoV2/COVID-19 pandemic represented an unprecedented emergency prompting a drive to minimise non-essential patient contact and the need for a virtual fracture clinic (VFC); an uncommon practice in paediatric units. Management of paediatric fractures requires a greater degree of vigilance to safeguard children. The current climate has created social challenges that theoretically increase the risk of harm and exploitation to children. This study investigates VFC in the management of paediatric fractures to determine the efficiency of such a process and the risk of safeguarding. Method: A protocol was devised in affiliation with BSCOS for the immediate management and streamlining of paediatric fractures into VFC. We retrospectively audited 235 VFC consults over a 1-month period. Patient sex was roughly evenly distributed, and age ranged from 9 months to 16 years (mean 8.4 years). Results: 42% of patients were recalled for a face-to-face (F2F) review (26% expedited), primarily for clinical assessment, plaster complaints and imaging requirements. 33% were discharged and 15% continued follow-up in VFC. All clavicle fractures were discharged. Forearm, hand, foot and elbow injuries were more likely to be discharged. Lower leg, upper arm and knee presentations more frequently required a F2F review. 2.3% of cases required safeguarding reviews. Conclusions: Given the rapid transition to VFC without the use of triage we have determined a number of non-complex fractures safely managed and discharged via VFC. The low percentage of recall due to safeguarding concern highlights this may not be a barrier to the continuation of virtual care outside of the context of a pandemic.